Bone Health in Patients with Multiple Sclerosis - Vit Zikan (Journal of Osteoporosis)
Multiple sclerosis (MS) is a gait disorder characterized by acute episodes of neurological defects leading to progressive disability. Patients with MS have multiple risk factors for osteoporotic fractures, such as progressive immobilization, long-term glucocorticoids (GCs) treatment or vitamin D deficiency. The duration of motor disability appears to be a major contributor to the reduction of bone strength. The long term immobilization causes a marked imbalance between bone formation and resorption with depressed bone formation and a marked disruption of mechanosensory network of tightly connected osteocytes due to increase of osteocyte apoptosis. Patients with higher level of disability have also higher risk of falls that combined with a bone loss increases the frequency of bone fractures. There are currently no recommendations how to best prevent and treat osteoporosis in patients with MS. However, devastating effect of immobilization on the skeleton in patients with MS underscores the importance of adequate mechanical stimuli for maintaining the bone structure and its mechanical competence. The physical as well as pharmacological interventions which can counteract the bone remodeling imbalance, particularly osteocyte apoptosis, will be promising for prevention and treatment of osteoporosis in patients with MS.